Students’ Experiences Using TikTok for Developing English Listening Skills: Pengalaman Mahasiswa Menggunakan TikTok untuk Pengembangan Keterampilan Mendengarkan Bahasa Inggris - Azzahro, Shania Zharfa Nur; Ahada, Ichi; Hermagustiana, Istanti; Amarullah, A. K (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Listening is a core component of second language development, yet students in English as a Foreign Language settings often struggle with fast speech, accent variation, and limited exposure to authentic English. Specific background: Social media, especially TikTok, has become a popular platform where learners encounter natural language use through short, engaging videos. Knowledge gap: However, little is known about how university students experience TikTok as a self-directed space for English listening development. Aim: This study explores students’ lived experiences using TikTok to support English listening skills. Results: Findings show that frequent exposure to authentic speech, short video formats, and interactive features such as duets and live sessions contribute to students’ listening development. Challenges arise from speech rate, accent diversity, slang, and algorithm-driven distractions. Students responded with self-regulated strategies, including curating content, replaying difficult segments, activating captions, and verifying information through external sources. Novelty: This study highlights students’ internal reflections and the role of algorithmic personalization as a source of individualized linguistic input. Implications: Results suggest that TikTok can serve as an informal listening environment that complements formal instruction and supports listening awareness, learning autonomy, and confidence among EFL university students. Highlights Students describe TikTok as a consistent source of authentic English input. Learners use self-regulation strategies to manage challenges and curate content. TikTok functions as an informal space that supports listening development and confidence. Keywords TikTok, English Listening Skills, Autonomous Learning, Phenomenological Study, Digital Learning